TRUST AND RISK PERCEPTION IN ONLINE APPAREL SHOPPING AMONG YOUNG WOMEN IN NAGPUR CITY - Jawalkar, Minakshi Nilkanth; P. Yende, Sonali P. Yende (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The quick boom of e-commerce has greatly modified the consumer shopping pattern especially among the young urban women in India. This paper discusses how trust and risky behavior influences online shopping behavior of young women in Nagpur City. Based on a descriptive research study design, with the collected data obtained with the help of 200 respondents and a designed questionnaire, the study outlines a variety of trust-building aspects, including secure payment systems, return policy, and product reviews, and lights upon the common problems with risk, including size and fitting problems, mismatched products, and fraud with payments. It can be seen that there is a positive relationship between trust and purchase frequency where risk perception and purchase intention are negatively associated. It is revealed that trust plays a pivotal role in ameliorating the perceived risk as well as to stimulate the online purchase. The study provides viable key recommendations to the online retailers so that they could explicitly gain more consumer confidence and minimize risk by enhancing its digital strategies, being more transparent and with reliable services.